Tissue-resident macrophages and renal diseases: landscapes and treatment directions - Qu, Zhuojian; Chu, Jinjin; Jin, Shuyu; Yang, Chunjuan; Zang, Jie; Zhang, Jin; Xu, Donghua; Cheng, Min (Frontiers in Immunology, 2025)
Tissue-resident macrophage (TRM) is a specialized subset of macrophage that resides within specific tissues and organs. TRMs play crucial roles in resisting pathogen invasion, maintaining the homeostasis of the immune microenvironment, and promoting tissue repair and regeneration. The development and function of TRMs exhibit significant heterogeneity across different tissues. Kidney TRMs (KTRMs) originate from both embryonic yolk sac erythro-myeloid progenitors and the fetal liver, demonstrating the capacity for self-renewal independent of bone marrow hematopoiesis. KTRMs are not only essential for the maintenance of renal homeostasis and the monitoring of microvascular environment, but contribute to renal injury due to inflammation, fibrosis and immune dysfunction in kidneys. In this review, we summarize currently available studies on the regulatory role of KTRMs in processes of renal injury and repair. The altering effects and underlying mechanisms of KTRMs in regulating local tissue cells and immune cells in different renal diseases are reviewed, primarily including lupus nephritis, diabetic nephropathy, renal fibrosis, and renal carcinoma. Understanding the plasticity and immune regulatory functions of KTRMs may offer new insights into the pathogenesis and the exploration of therapeutic strategies of kidney diseases.